READING INTERESTS AND INFORMATION SOURCES OF SCHOOL GOING CHILDREN : A CASE STUDY OF TWO ENGLISH MEDIUM SCHOOLS OF ROURKELA, INDIA - Panigrahi, Chittaranjan; Panda, Krushna Chandra; Panigrahi, Chittaranjan; Panda, K.C. (Malaysian Journal of Library and Information Science, 2017)
Studies the reading interest and information eliciting sources of 130 school going children of two leading English-medium schools in Rourkela, India and identifies factors that hinder the development of reading interests. Suggests measures required for improvement.